Design and Implementation of Management Information System for Research and Community Engagement Activities (Nusantara Science and Technology Proceedings, 2021)
Since 2019, UPN “Veteran” Jawa Timur has been awarded a predicate of “Klaster Mandiri” (Self-Governing Cluster) in terms of research based on the assessment of university research performance in 2016-2018. The status has a direct impact on the increasing number of research funds that can be managed internally by LPPM. However, in managing its activities related to the implementation of independent grants, LPPM faces challenges. Especially in the last two years, the pandemic of Covid-19 has forced any organization, including LPPM, to find an alternative way to the restricted face-to-face interaction. Hence, many activities such as submitting research proposals or progress reports previously carried out offline had to be done online. However, the tools used to exchange and store data (soft-copy files) are still very simple since LPPM only uses e-mail and google drive. The disadvantage of this method is that documents are vulnerable to lose, and if there is an urgent request for data that must be quantified, it is difficult to fulfill. Therefore, it is necessary to transform the business processes to facilitate online interaction as an alternative and complement to offline interaction and improve the quality of the research administration. This change in business processes is implemented by an application named SIMARIS which will be the focus of discussion in this paper. SIMARIS is developed using the V Model and ICONIX process. As a reference in the coding stage, UML diagrams generated from the Iconix process will be used. The application was developed using the PHP CI 3 framework and then tested using the Black-Box method. The results of the black box testing confirm that all features that have been developed match the user's requirements. This application is intended to be used by lecturers and mainly by LPPM to better manage its self-governing research and community engagement activities.